If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 4y = 14 Solving -9x + 4y = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -9x + 4y + -4y = 14 + -4y Combine like terms: 4y + -4y = 0 -9x + 0 = 14 + -4y -9x = 14 + -4y Divide each side by '-9'. x = -1.555555556 + 0.4444444444y Simplifying x = -1.555555556 + 0.4444444444y
| X^2=y+12 | | 8x=36x | | 500-335= | | 48t^2-28t+2=0 | | 2x^2+10x=-6 | | -41=-2-13n | | 0=36p^2-31 | | 4x*2+8x-32=0 | | 0=36p^2-9 | | 40=36p^2-9 | | 9x*2-21=0 | | (x-4)(x+8)=64 | | -13+y=-24 | | 13+y=-24 | | -13y=-24 | | 6x^3+4x=10x^2 | | 5x-7=3x-10 | | 5x+24(x-4)=107 | | 4x-3+2x=8x | | 6+k=14 | | (2x^2+3x-2)(3x^2-6x-5)= | | n-4=24 | | 23=-2(24-b)+3(b-3) | | 15x+21(x-2)=318 | | 4x^2+7-3=0 | | 19x-(4x-9)=84 | | 19x-3(4x-9)=84 | | 5m+10=9m-2 | | 5(6z+1)-9=146 | | 3(4x-1)=36 | | (-6)(9)= | | (4-9)= |